The Role of Community Engagement in Successful Recruitment of Research Participants During the COVID-19 Pandemic - Kyra Oziel; Jessica D. Hanson; Karen Little Wounded; Serea Darnell; Dedra Buchwald (Health Equity)
Background: Our research team was in the process of recruiting American Indian and Alaska Native (AIAN) women for a community-based intervention to prevent alcohol-exposed pregnancy when the COVID-19 pandemic began. Safety measures adopted at the tribal, state, and national level required us to rethink and revise study protocols. We followed the principles of community-based participatory research, especially community engagement. The goal of this article is to report the recommendations from local AIAN field staff and the community advisory board that enabled us to exceed our prepandemic recruitment goal. Methods: First, we developed a list of major adaptations and mapped each one onto our recruitment timeline to assess its effect on subsequent enrollment. Second, we surveyed the two AIAN field staff who led recruitment and an administrative staffer at the study site and conducted a qualitative analysis of their responses. Results: Our revised project timeline presents the major adaptations that led to our successful recruitment, as verified by qualitative data from field staff. These adaptations included expanding our social media presence, expanding recruitment to a nearby urban site, implementing a “refer a friend” program, and recruiting through local media outlets. Most important was having local AIAN staff who cultivated a nonjudgmental space for potential participants to talk about sensitive topics. Discussion: We not only met our prepandemic recruitment goal but exceeded it by 16.6%. The input of our community advisory board and the efforts of community-based staff were essential in achieving success during the unprecedented conditions of the COVID-19 pandemic.